2019
DOI: 10.1155/2019/2796126
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for the Calculation of the Intraocular Lens Power Based on the Fictitious Corneal Refractive Index Estimation

Abstract: Purpose. To identify the sources of error in predictability beyond the effective lens position and to develop two new thick lens equations. Methods. Retrospective observational case series with 43 eyes. Information related to the actual lens position, corneal radii measured with specular reflection and Scheimpflug-based technologies, and the characteristics of the implanted lenses (radii and thickness) were used for obtaining the fictitious indexes that better predicted the postoperative spherical equivalent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, knowing the geometry of the IOL makes it possible using a thick lens paraxial model to relate the optically estimated position of an IOL to its estimated anatomic position. Fernández et al 22 studied the relationship between the measured ALP and the back-calculated ELP and demonstrated the differences between both values, induced by assumptions made in theoretical eye models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knowing the geometry of the IOL makes it possible using a thick lens paraxial model to relate the optically estimated position of an IOL to its estimated anatomic position. Fernández et al 22 studied the relationship between the measured ALP and the back-calculated ELP and demonstrated the differences between both values, induced by assumptions made in theoretical eye models.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 This finding is reflected in a recent study 27 in which there was no significant difference in the accuracy of thick lens IOL power formula based on calculated versus manufacturer's IOL data for eyes with ALs of 22 mm and more. Fernández et al 22 suggested modifying the refractive index of the cornea to correct errors beyond the ELP prediction, including assumptions from the biometers.…”
Section: Discussionmentioning
confidence: 99%
“…A ccuracy in intraocular lens (IOL) power calculation has become a topic arousing great interest, because nowadays crystalline-lens replacement can be considered not only for the surgical treatment of an ocular disease but also for a refractive surgery procedure. 1 New formulas and updates to existing ones have been proposed in the last years, but refractive-status prediction errors greater than ± 0.50 diopters (D) still occur in a rather high percentage of cases-which ranges between 8% and 50% of the eyes, depending on the specific study or sample stratification, [2][3][4][5][6][7][8][9] -with the best accuracy obtained for multifocal IOL implantation procedures, and the vast majority of surgeons being clustered around 78%. 5,10 The major part of the methods for IOL power calculation is based on the vergence formula, and the main difference lies in the estimation of the effective lens position including from 2 up to 7 variables, some of them corresponding to eye parameters.…”
mentioning
confidence: 99%
“…These include regression and vergence methods, employing “thin lens” and “thick lens” models as well as ray-tracing methods. [ 3 4 5 ]…”
mentioning
confidence: 99%
“…This provides us with a set of formulae, where each is more appropriate for a given range of axial length than the other. [ 3 4 5 ] The Hoffer-Q formula is most accurate in eyes with a shorter AL while SRK/T and Haigis formulae are better suited for eyes with longer AL. The accuracy of these formulae may differ according to the ACD, even in eyes with the same AL and keratometry.…”
mentioning
confidence: 99%